Effect of Variation of Quenching Process Cooling Media on Hardness and Microstructure of AISI 1020 Steel Subjected to The Pack Carburizing Process Using Graphite and Eggshell Carbon Media - Zulhanif, Zulhanif; Supriadi, Harnowo; Prihastomo, Sigiet; Hanif, Muhammad; Ummah, Khairul (INSTEP Network, 2024)
AISI 1020 steel is a low carbon steel which has a low selling price compared to medium carbon steel, high carbon steel, and alloy steel. This material is used as a construction material. in general, it is widely used and applied to machine components and construction components such as gears and shafts with relatively small loads. The purpose of this research is to increase the value of hardness. The pack carburizing process is carried out using graphite carbon media and egg shells at a temperature of 850 ºC. This process can increase the hardness of a material. The highest hardness value was obtained with the brine cooling medium of 457,111 BHN, then the water-cooling medium of 319,345 BHN, and finally the oil cooling medium of 248,204 BHN.